AN ASSESSMENT OF THE VARIOUS MITIGATION STRATEGIES TO COMBAT DESERTIFICATION IN JIBIA AND KAITA LOCAL GOVERNMENT AREAS OF KATSINA STATE - Richard Sunday Thlakma; John Eche Omale (Geosfera Indonesia, 2019)
This study was conducted on an assessment of the various mitigation strategies to combat desertification in Jibia and Kaita Local Government Areas of Katsina State, Nigeria. The data use includes Satellite imageries for the study such as landsat MSS of 1976, landsat TM of 1987, SPOT XS of 1995 and landsat ETM of 2006 as well as structured questionnaires. Sixty close ended copies of the Questionnaire were administered in the study. Purposive sampling method of administering questionnaires was adopted. The percentages land mass covered for each of these variables was determined and estimated in M2. literature was obtained from various agencies which were responsible for desertification control in Katsina state. It was found from the reserved forest that in 1976 the percentage of reserved forest was 2.57%. In 1987 however, it increased by 73.9% to 76.47 %. By 1995, it declined by 9.42% to 67.05% and further declined by 0.52% in 2006. Effort to combat desertification through the use of reserved forest has been quite significant over the years. Also, noticed was a declined in shelter belt from 5.91% in 1987 to 1.097% in 1995 and a shot up to 7.39% in 2006. About 37% of the respondent opined that the deforestation leads to the disappearance of trees while 33% pinioned that it leads to reduction on agricultural productivity. The major strategy adopted to combat desertification is tree planting as supported by 88% of the respondents. It found that desertification as major environmental problem of the study area has reduced drastically from 43.34% in 1976 to 1.29% in 2006. It was also revealed from this study that some organizations such as European Economic Community/Katsina State government EEC/KTSG, Katsina Afforestation Project Unit KTAPU and Local Government Councils are the major agencies that are responsible for mitigating desertification in the study area. Keywords: Desertification, Mitigation, Afforestation, Shelterbelt and Satellite image References Ariyo, J.A, Abdullahi, C.J. Stigter, O.Z Onyewotu and I. Musa (2005). Community Participation in Planning Desertification, Control Interventions in Northern Nigeria. Lessons from Kano State. A Paper Presented at the Conference on Prospects and Problems of Agricultural Development in Nigeria, Held in Ahmadu Bello University Zaria. June 29th – July 2nd, 2005. Auwal, U. (2006). An Appraisal of Desertification in Arid Zone of Bauchi State. Unpublished PGDEM thesis Department of Geography, Bayero University Kano. Babura, D.U. (2001). Desertifucation in Babura Local Government Area. Unpublished PGDEM Thesis. Department of Geography, Bayero University Kano. Bala, A. (2003). An Evaluation of Drought Incidence and Hazards in Northern Nigeria. A Paper Presented at a Seminar on the Conservation of the environment. Department of Geography Isa Kaita College of Education, Dutsinma, Katsina State 5th November. Bins, T. (1990). The Threatening Deserts: Ox Blackwell. Campbell, D.J (1986). The Prospects For desertification in Kajiado District Kenya, Geg. Federal Office of Statistics (1999). Annual Abstracts of Statistics: facts and Figures about Nigeria. Katsina Afforestation Project Unit (2006). A brief on Katsina Afforestation Project Unit (FGN ASSISTED) 1st February, 2006. Katsina Afforestation Project Unit (2006). Annual Reports on Afforestation Projects. Katsina Afforestation Project Unit (2009). Annual Reports on Afforestation Project. Katsina Afforestation Project Unit KTAPU. (2009). A brief on Katsina Afforestation Project Unit (FGN ASSITED) 5th February, 2009. Katsina Agricultural and Rural Development Authority KTARDA. (2006). Land Management\ Unit, Historical Background to soil conservation in Katsina State. Katsina Arid Zone Programme EEC/KTSG (1995). Soil Conservation Experience, A paper for KSACDP one day Soil conservation Strategy Workshop 14th December, 1995. Katsina Arid Zone Programme EEC/KTSG. (1995). Historical background of soil conservation efforts in Katsina State. Msafirri, F. (2009). Involving or not Involving Communities in strategies to combat Desertification and Drought in Kenya. Murtala S.K. (2003). An Analysis of the problems of desertification in Katsina local government area. An NCE project, Isa kaita College of Education Dutsin Ma, Katsina state. Nasiru, I.M. (2009). Combating Desertification and Drought in Nigeria. Daily Trust Monday, 25th. National Population Commission (2006). Federal Republic of Nigeria (2009), National Population Commission Official Gazette No2, Abuja 2nd February 2009 Vol 96. Njeru, J. (2005). Monitoring and Modelling crop growth, water use and production crop growth, water use and production under dry land environment, north west of mount Kenya. Nyong, A.O. and Kanoroglou, P.S (1999). The Influence of water resources and their locations on rural distribution in north eastern Nigeria. A journal of environmental sciences. Owen and Pickering (1997). Global environmental issues. Rutledge and New York. Sagua, V.O, Enabor, E.E, K.O P.R.O, Ojanuga A.V, Mortimore, M. and Kalu, A.E. (1987). Ecological Disasters in Nigeria. Drought and Desertification Federal Ministry of science and Technology Lagos. Sani, M. (1996). Evaluation of Desertification and its effects in Jibia local Government area of Katsina state. Unpublished PGDEM Thesis. Department of Geography Bayero University Kano. Shittu, K. (1999). An Assessment on the socio economic effects of desertification in Katsina state. An Unpublished BSC project Department of Geography Bayero University Kano. Stebbing, E.P. (1935). The Encroaching Sahara: The Threat to west Africa colonies. A geographical Journal. The United Nations Convention to Combat Desertification (1997). A new Response an age – old problem. United Nations Conversation on Desertification (1977). Desertification, it Causes and Consequences: Pergmon Press. United Nations, Department for Public Information (1997). The United Nations convention to combat desertification. Whates and Jones (1992). Land Degradation. Edward Arnold London. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License